The virtues of liberalism - Kloppenberg, James T. (Oxford University Press, 1998)
This spirited analysis and defence of American liberalism demonstrates the complex and rich traditions of political, economic, and social discourse that have informed American democratic culture from the seventeenth century to the present. The Virtues of Liberalism provides a convincing response to critics right and left. In contrast to prevailing tendencies to simplify and distort American liberalism, Kloppenberg shows how the multifaceted virtues of liberalism have inspired theorists and reformers from Jefferson and Madison through Jane Addams and John Dewey to Martin Luther King Jr., and how these virtues persist in the work of liberal democrats today. Endorsing the efforts of such neo-progressive and communitarian theorists and journalists as Michael Walzer, Jane Mansbridge, and Michael Sandel, Kloppenberg adds a more acute analysis of the historical development of American liberalism and of the complex reasons why it has been transformed and made more vulnerable in recent decades.; At a time when conservatives join radicals in distorting the development of liberalism and underestimating its resources, Kloppenberg offers a probing historical analysis and reassessment of the theory and practice of liberalism today.